2011
DOI: 10.1021/om200612h
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Trivalent U–C, U–N, and U–S Bonds and Their Reactivity toward Carbon Dioxide and Acetone

Abstract: A family of uranium(III) complexes of the form Tp*2UX (Tp* = hydrotris(3,5-dimethylpyrazolyl)borate, X = CCPh (2-CCPh), CCSiMe3 (3-CCSiMe 3 ), NHPh (4-NHPh), NHCH2Ph (5-NHCH 2 Ph), SPh (6-SPh)) have been synthesized in quantitative yields by protonation of the benzyl group Tp*2U(CH2Ph) (1-CH 2 Ph) with organic precursors. Full characterization of these complexes, which contain newly formed uranium–carbon, uranium–nitrogen, and uranium–sulfur bonds, was performed using 1H NMR and IR spectroscopies. These d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
98
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 56 publications
(118 reference statements)
9
98
0
Order By: Relevance
“…The U-N bond lengths, ranging from 2.542(4) to 2.739(3) Å, are in agreement with typical U-N bond lengths seen for bis-Tp* supported uranium(III) species. [12][13][14] As expected, the terminal U-F distance of 2.156(3) Å is shorter than the analogous U-X distances reported for Tp* 2 UCl (2.698 Å) and Tp* 2 UI (3.220 Å). To the best of our knowledge, this complex represents the first crystallographically characterized terminal uranium(III) fluoride.…”
supporting
confidence: 75%
“…The U-N bond lengths, ranging from 2.542(4) to 2.739(3) Å, are in agreement with typical U-N bond lengths seen for bis-Tp* supported uranium(III) species. [12][13][14] As expected, the terminal U-F distance of 2.156(3) Å is shorter than the analogous U-X distances reported for Tp* 2 UCl (2.698 Å) and Tp* 2 UI (3.220 Å). To the best of our knowledge, this complex represents the first crystallographically characterized terminal uranium(III) fluoride.…”
supporting
confidence: 75%
“…bibenzyl was noted, as determined by integration against a ferrocene internal standard. [12,13,[16][17][18] Compound 2 features a short U1-N41 (diazomethane Nα) bond length of 2.146(7) Å, which is indicative of uranium-nitrogen mulwww.eurjic.org [20] commonly show longer U-N bonds. of the diazoalkane with the uranium(III) species Tp* 2 U(2,2Ј-bpy), which has a monoanionic bipyridine ligand.…”
Section: Resultsmentioning
confidence: 99%
“…[15] Hence,d eveloping atom-efficient, versatile catalytic systems for their preparation represents amajor challenge in the field of homogeneous catalysis,e specially because the respective metal catalyst is required to display at olerance toward functional groups and heteroatoms.Previous studies by Evans et al have shown that carbodiimides can effectively insert into the AnÀC(An = Th,U)bond of Cp* 2 An(CH 3 ) 2 ,yielding mixed cyclopentadienyl actinide amidinate complexes in high yield. [20] It should be noted, however, that these actinide species have not been investigated as part of acatalytic process. [20] It should be noted, however, that these actinide species have not been investigated as part of acatalytic process.…”
mentioning
confidence: 99%
“…[21] Thus,w ed ecided to investigate the substantial question whether the stoichiometric reactivity toward carbodiimides displayed by organometallic actinide complexes [16,20] can be incorporated into ac atalytic cycle by the protonolytic cleavage of the AnÀN bond, formed by the insertion of the carbodiimide,w ith different families of R À E À H( E= N, P, S; R= alkyl, aryl, H) moieties,y ielding actinide amido,p hosphido,a nd sulfide intermediates.T herefore,w es et out to study the catalytic activity of actinide coordination complexes toward different families of heterocumulene systems and REH moieties,i n which Ei san ucleophilic element, expanding the scope of accessible products.Owing to the high activity,selectivity,and tolerance toward functional groups displayed by 1 in the Tishchenko reaction, [21] the thorium compound 1 was applied for all further catalytic studies with heterocumulenes presented herein. (1)],can be used as an active catalyst for the dimerization of aldehydes,displaying high catalytic activity and selectivity toward the formation of asymmetrically substituted esters.…”
mentioning
confidence: 99%